Measurements of self-guiding of ultrashort laser pulses over long distances. (31st October 2017) - Poder, K; Cole, J M; Wood, J C; Lopes, N C; Alatabi, S; Foster, P S; Kamperidis, C; Kononenko, O; Palmer, C A; Rusby, D; Sahai, A; Sarri, G; et al.
Abstract: We report on the evaluation of the performance of self-guiding over extended distances with f / 20 and f / 40 focussing geometries. Guiding over 39 mm or more than 100 Rayleigh ranges was observed with the f / 20 optic at n e = 1.5 × 10 18 cm − 3 . Analysis of guiding performance found that the extent of the exiting laser spatial mode closely followed the matched spot size predicted by 3D nonlinear theory. Self-guiding with an f / 40 optic was also characterised, with guided modes observed for a plasma length of 90 mm and a plasma density of n e = 9.5 × 10 17 cm − 3 . This corresponds to self-guided propagation over 53 Rayleigh ranges and is similar to distances obtained with discharge plasma channel guiding.